Design and Analysis of Hybrid Vessel Monitoring System based on DTN and Internet Collaboration - Basuki, Akbari Indra; Wuryandari, Aciek Ida (Pusat Penelitian Informatika - LIPI, 2015)
In this paper, we propose hybrid Vessel Monitoring System (VMS) design as alternative for current VMS scheme by collaborating internet connection and Disruption-Tolerant-Networks (DTN). The hybrid solution combines offline VMS that use radio networks and online VMS that utilizing satellite-based internet. Hybrid VMS aims to provide a more flexible VMS design and able to speed up delivery process of offline vessel’s data. The concept is both type of vessels must install a standard radio networks for data forwarding. The proposed method to speed up data delivery is by forwarding VMS data from one vessel to another using DTN forwarding scheme. Data can be forwarded to another offline vessel that will return to harbor earlier or to online vessels which have internet connection. Performance measurement is done through simulation analysis using ONE simulator. It aims to measure the speed up data delivery using hybrid VMS implementation compare to a pure offline VMS implementation. Simulation result show that hybrid VMS able to speed up data delivery for offline vessel data in 1.5 up to 2 times faster compare to a pure offline VMS implementation. Hybrid VMS also has advantages in flexible implementation by easily switching between online and offline VMS scheme, according to fisherman financial situation. Spray-and-Wait routing is the most suitable routing algorithm for hybrid VMS according to the efficiency ratio.